Optimal N management affects the fate of urea-15N and improves N uptake and utilization of wheat in different rotation systems - Ma, Quan; Dai, Dandan; Cao, Yifan; Yu, Qiaoqiao; Cheng, Xiyang; Zhu, Min; Ding, Jinfeng; Li, Chunyan; Guo, Wenshan; Zhou, Guisheng; Zhu, Xinkai (Frontiers in Plant Science, 2024)
Rice-wheat and maize-wheat rotations are major cropping systems in the middle and lower reaches of Yangtze River in China, where high nitrogen (N) inputs and low N efficiency often exacerbate resource waste and environmental pollution. Due to the changes in factors such as soil properties and moisture content, the N fate and the N utilization characteristics of wheat in different rotations are significantly different. Efficient N management strategies are thus urgently required for promoting maximum wheat yield in different rotation systems while reducing N loss. A 2-year field experiment using 15 N tracer technique was conducted to evaluate the fate of 15N-labelled urea in wheat fields and the distribution characteristics of N derived from different sources. The wheat yield and N use efficiency under various N rates (180 and 240 kg ha -1 , abbreviated as N180 and N240) and preceding crops (rice and maize, abbreviated as R-wheat and M-wheat) were also investigated. The results showed that N240 increased N uptake and grain yield by only 8.77-14.97% and 2.51-4.49% compared with N 180, but decreased NAE and NPE by 14.78-18.79% and 14.06-31.35%. N240 also decreased N recovery in plants by 2.8% on average compared with N180, and increased N residue in soil and N loss to the environment. Compared with that of basal N, the higher proportion of topdressing N was absorbed by wheat rather than lost to the environment. In addition, the accumulation of topdressing N in grain was much higher than that of basal N. Compared with that in R-wheat treatment, plants in M-wheat treatment trended to absorb more 15 N and reduce unaccounted N loss, resulting in higher yield potential. Moreover, the Mwheat treatment increased N recovery in 0-20 cm soil but decreased 80-100 cm soil compared with R-wheat treatment, indicating a lower risk of N loss in deeper soil. Collectively, reducing N application rate and increasing the topdressing ratio is an effective way to balance sustainable crop yield for a secure food supply and environmental benefit, which is more urgent in rice-wheat rotation.